Plant-based vaccines and antibodies to combat COVID-19: current status and prospects - Kuldeep Dhama; Senthilkumar Natesan; Mohd. Iqbal Yatoo; Shailesh Kumar Patel; Ruchi Tiwari; Shailendra K Saxena; Harapan Harapan (Taylor & Francis Group, 2020)
Globally, researchers are undertaking significant efforts to design and develop effective vaccines, therapeutics, and antiviral drugs to curb the spread of coronavirus disease 2019 (COVID-19). Plants have been used for the production of vaccines, monoclonal antibodies, immunomodulatory proteins, drugs, and pharmaceuticals via molecular farming/transient expression system and are considered as bioreactors or factories for their bulk production. These biological products are stable, safe, effective, easily available, and affordable. Plant molecular farming could facilitate rapid production of biologics on an industrial scale, and has the potential to fulfill emergency demands, such as in the present situation of the COVID-19 pandemic. This article aims to describe the methodology and basics of plant biopharming, in addition to its prospective applications for developing effective vaccines and antibodies to counter COVID-19.